Comparative Assessment on Linearity Test based V2π and Vπ/2 Voltage Variations of Closed Loop IFOG - T. Sireesha; K. Krishna Murthy (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Interferometric Fiber Optic Gyroscope (IFOG) has to operate in closed loop condition to achieve inertial grade performance. The closed loop system is mainly depends upon the amplitude of the ramp signal (V2π of IOC) and bias (square wave) signal frequency (fbias). The digital phase ramp function is given as feedback to the optical system and makes gyro to null condition. The peak-to-peak amplitude (Vπ/2) of biasing signal is one-fourth of the ramp amplitude (V2π). If there are any variations in the amplitude of the ramp and biasing signals, then it introduces variations in the gyro performance. In this paper, a comparative discussion made in the gyro parameters for three cases: (i) V2π (vary) & Vπ/2 (constant), (ii) Vπ/2 (vary) & V2π (constant) and (iii) both V2π and Vπ/2 are varying simultaneously. The effects on gyroscope are described with the derived values in terms of linearity. From the experimental results, it was observed that the gyro output is very sensitive with respect to V2π variations and obtained the percentage error of 10% in gyro output, but very less effect due to Vπ/2 variations. So, the proper resetting of ramp voltage (V2π) is required to avoid nonlinearities and instabilities in gyro output.